Akuntabilitas Pengelolaan Anggaran Tahun 2014-2015 Pada Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Kabupaten Bone - Agustiani Agustiani; Nahariah Nahariah (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study aims to find out (1) What is the description of the implementation of performancebased Budget management accountability at the Regional Financial and Asset Management Agency of the Regency. Bone. (2) Constraints in implementing performance-based Budget Management accountability at the Regional Financial and Asset Management Agency, Kab. Bone. (3) What is the solution to the obstacles to the implementation of performance-based Budget Management accountability at the Regional Financial and Asset Management Agency of the Regency. Bone. The results of this study indicate that in the budget management accountability activities at the Regional Financial and Asset Management Agency in Kabupaten Bone, it has implemented 4 (four) accountability principles, namely budget planning, budgeting, budget execution, and budget accountability. However, there are still obstacles from the application of budget management accountability principles, namely weaknesses in Human Resources and Coordination in budgeting. As for the solutions to these constraints, as long as they are adapted to existing activities, follow the schedule and need more maximal socialization to the parties. party responsible for caramusyawaramufakat Regional Government Budget Team.